Theories of Equity in Health Care, Implications for Developed and Developing Countries - AR Olyaee Manesh (Tehran University of Medical Sciences, 2005)
Objective: This abstract focuses on theoretical background for the notion of "equity in health care" and on the implications of applying these theories to the health care of developed and developing countries. Equity Principals and the Implications: There are different theories about the principle of Equity or Justice such as Altruism, Utilitarians, Marxists, Rawls' theory and Nazick's entitlement. Among these theories, some of them are applicable to health care such as Libertarianism and Egalitarianism. The focus of the Libertarians is on the extent to which people are free to purchase the health care that they want. The Libertarians' principle is the main equity base for private health systems. In contrast, Egalitarians suggest that finance of the health care should be according to the ability to pay and distribution of health care should be according to the need (ill health). It seems that policy makers in most developed countries such as European countries accept the Egalitarians' principle and application of this equity principle by their health systems has significantly reduced health inequities and inequalities in these countries. There are a limited number of studies to look at equity in the health care of developing countries. A common equity principle for these countries is "equal access for everyone" and different mechanisms are applied to attain this target. Despite the overall improvements in health care in recent years, evidence indicates that many of developing countries have failed to provide equal access to health care for all in need. The financial limitations of the governments, spending about 70% of the health care resources on hospital-based care, unequal access to hospital services in favour of urban population, income inequalities among population, and lack of consistent and up-to-date information of inequalities, make developing countries unable to monitor and prevent inequities and inequalities of health care. Conclusion: The main equity principle in the health care of developed countries is Egalitarians' principle in which, health care should be financed according to ability to pay and should be delivered according to the need. Applying the equity principals to the health care of developed countries has deeply promoted equitable health care in these countries. There are a limited number of studies about this issue in developing countries. A common equity target in these countries is "equal access for everyone in need" which is close to the Egalitarians' point of view. However, some factors have hampered these countries' attempts to achieve their equity goals. To be able to attain their equity targets, these countries need to reduce income and economic inequalities, to provide consistent and up-to-date information of the existing health inequities and to consider reallocation of limited health resources from hospital services to the basic preventive and curative care. Further evidence is needed to assess the issue of equity in the health care of developing countries.